1998
DOI: 10.4049/jimmunol.160.10.5073
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Receptors for C5a Anaphylatoxin (CD88) on Human Bronchial Epithelial Cells: Enhancement of C5a-Mediated Release of IL-8 upon Exposure to Cigarette Smoke

Abstract: Results are presented that demonstrate a heightened responsiveness of human bronchial epithelial cells (HBECs) toward the complement-derived anaphylatoxin C5a when these cells are exposed to cigarette smoke. This C5a response is possible because we show at both the protein and mRNA levels that HBECs constitutively express receptors for C5a (C5aR, CD88). Control (untreated) HBECs responded to C5a (50 nM) by releasing the proinflammatory cytokine IL-8 at low but significant levels. However, exposure of HBECs to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…7 In addition, we have shown that receptors for complement factor 5a (C5a) are constitutively present on the surface of HBEC and that CSE exposure initiates an increase in the population of C5a receptor-positive cells. 8 We have also shown that IL-8 release in response to CSE is increased significantly if HBEC are subsequently treated with C5a. 8 It seems that exposure of HBEC to CSE enhances the responsiveness of the C5a receptor on these cells to C5a-mediated release of IL-8.…”
Section: Introductionmentioning
confidence: 62%
See 4 more Smart Citations
“…7 In addition, we have shown that receptors for complement factor 5a (C5a) are constitutively present on the surface of HBEC and that CSE exposure initiates an increase in the population of C5a receptor-positive cells. 8 We have also shown that IL-8 release in response to CSE is increased significantly if HBEC are subsequently treated with C5a. 8 It seems that exposure of HBEC to CSE enhances the responsiveness of the C5a receptor on these cells to C5a-mediated release of IL-8.…”
Section: Introductionmentioning
confidence: 62%
“…8 We have also shown that IL-8 release in response to CSE is increased significantly if HBEC are subsequently treated with C5a. 8 It seems that exposure of HBEC to CSE enhances the responsiveness of the C5a receptor on these cells to C5a-mediated release of IL-8. In addition, we demonstrated that CSE activates protein kinase C (PKC) and that PKC activation is required for CSE-enhanced C5a-mediated release of IL-8 in HBEC.…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations